Uptake of Fe, Mn, Zn, Cu, and B in a cucumber (Cucumis sativus L.) crop (2018)
Cucumber cultivation increases dry matter accumulation and yield when macronutrients and micronutrients are provided at levels that meet  their nutritional extraction. In the case of micronutrients, there is no accurate information on the quantities extracted by this crop when it is sown in a hydroponic system with nutrient solutions, which can lead to excessive applications or nutritional deficiencies. Therefore, this study was conducted at the Universidad Autónoma Chapingo, México, under greenhouse conditions with hydroponic cultivation using a random block experiment design and four treatments consisting of different concentrations of the universal nutrient solution of Steiner: 25, 75, 125 and 175%, in order to determine the yield, the amounts of Fe, Cu, Zn, Mn and B extracted by the aerial part of the crop and the absolute extraction rate. According to the results, the yield was 8.20 kg/plant with the 175% nutrient solution,and, for the  25, 75 and 125% solutions, the yield was 40, 78 and 85%, respectively, of the yield obtained with the 175% solution. For the production of  1 t of fruits, the crop extracted 41.74, 34.90, 12.01, 40.84 and 36.91 g of Fe, Cu, Zn, Mn and B, respectively.